2011
DOI: 10.1258/ar.2011.100514
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery embolization for emergent management of postpartum hemorrhage associated with placenta accreta

Abstract: UAE appears to be a safe and effective means by which to control PPH associated with PA. PA complicated by uterine atony or placenta previa may be at increased risk of UAE failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 21 publications
(40 reference statements)
1
26
1
Order By: Relevance
“…Criteria of failed TAE include disseminated intravascular coagulation [18,19,75,76], major transfusion (i.e., transfusion [5 or 10 red blood cell packs), blood loss [1.5L [18,19,40], severe arterial vasoconstriction at the time of TAE [56], and invasive placenta, which has a failure rate of approximately 20 % [24,25,67]. It has been suggested that repeat TAE may be more frequently needed in women with active extravasation at initial angiography [60].…”
Section: General Results and Causes Of Failurementioning
confidence: 99%
See 2 more Smart Citations
“…Criteria of failed TAE include disseminated intravascular coagulation [18,19,75,76], major transfusion (i.e., transfusion [5 or 10 red blood cell packs), blood loss [1.5L [18,19,40], severe arterial vasoconstriction at the time of TAE [56], and invasive placenta, which has a failure rate of approximately 20 % [24,25,67]. It has been suggested that repeat TAE may be more frequently needed in women with active extravasation at initial angiography [60].…”
Section: General Results and Causes Of Failurementioning
confidence: 99%
“…In women with invasive placenta, TAE has a success rate of approximately 80 % [23][24][25][26][27], with 20 % of women requiring further surgery and hysterectomy [23,27,88] and a complication rate of 11 %, including uterine necrosis, endometritis, and synechiae [88,89].…”
Section: Retained and Invasive Placentamentioning
confidence: 99%
See 1 more Smart Citation
“…8 Only Three patients underwent a hysterectomy after UAE failed to stop the bleeding. They also reported UAE appears to be a safe and effective means by which to control PPH.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Many researchers have focused on patient radiation exposure in UAE. Nikolic et al 2 reported that the absorbed ovarian dose and absorbed skin dose during UAE could be reduced by using pulsed fluoroscopy instead of nonpulsed fluoroscopy.…”
Section: Discussionmentioning
confidence: 99%